Near-infrared quantum dots for light-emitting devices and preparation method and application thereof

CN119529843BActive Publication Date: 2026-10-16MINDU INNOVATION LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311583782.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2026-10-16
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

[0004]目前研究的近红外量子点主要为II-VI族和IV-VI族半导体,如CdSe、CdTe和PbSe等,虽然具有较好的光学性质,但是其组分中的重金属元素(Cd2+和Pb2+等)是美国及欧盟等国家和地区严格限制的

Benefits of technology

[0060] This invention has the following advantages: 1) The near-infrared quantum dot phosphor has good photothermal stability, with a yield of over 80%, reaching up to 92.8%. It has high light absorption efficiency, effectively prevents blue light leakage, can be excited by various chips (UV, blue, and red), has wide applicability, excellent resistance to damp heat, and a long service life; 2) The near-infrared quantum dots in this invention do not contain toxic Pb/Cd heavy metals, conforming to the concept of green chemistry; 3) The quantum dots maintain excellent dispersibility in encapsulation adhesives and inkjet inks, preventing luminescence quenching caused by aggregation; 4) Quantum dot luminescent arrays with a size less than 30 μm can be prepared, exhibiting high luminescence intensity, regular shape, and no coffee rings, compared to... The chip cutting and mass transfer process is simpler, cheaper, and more repeatable, enabling large-scale production; 5) The inventors unexpectedly discovered that when preparing the core structure of near-infrared quantum dots, only when the oleylamine and dodecyl mercaptan used to dissolve Se powder are in a specific ratio (2-3):1 can near-infrared quantum dots with a quantum yield greater than 90% be obtained. Under other ratio conditions, the quantum yield drops sharply; 6) In this invention, when quantum dots are used in micro-LEDs, they are first configured into ink and then printed onto the surface of the LED chip. The contact angle between the contact layer on the LED chip surface and the ink is 10-30°, which makes the ink print without trailing and forms a uniform structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529843B_ABST
    Figure CN119529843B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of luminescent materials, and relates to a near-infrared quantum dot for a light-emitting device, a preparation method and application of the near-infrared quantum dot, and the light-emitting device is provided with the near-infrared quantum dot or a fluorescent powder including the quantum dot, and the light-emitting device is a mini-LED or a micro-LED, the mini-LED or the micro-LED includes a corresponding LED chip, and the LED chip is provided with the near-infrared quantum dot or the fluorescent powder. The near-infrared quantum dot fluorescent powder has good light-heat stability, the yield of the near-infrared quantum dot is greater than 80%, and can be up to 92.8% at most, has high light absorption efficiency, can well prevent blue light leakage, can be excited by ultraviolet-blue-red multiple chips, has wide application scenarios, has excellent moisture and heat resistance, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of luminescent materials, and relates to a near-infrared quantum dot for light-emitting devices, its preparation method and application, and particularly to a quantum dot phosphor with Pb / Cd-free near-infrared emission, its preparation method and an LED light source containing the phosphor. Background Technology

[0002] Since its introduction by Chinese scientist Professor Jiang Hongxing in 2000, Micro-LED has sparked a global wave of research, demonstrating broad application prospects in fields such as super-resolution displays, artificial intelligence, and wearable electronic devices. Micro-LED has become a key technological focus in international competition, and my country has also invested heavily in its research. Currently, research on micro-LED mainly concentrates on the visible light region. Near-infrared light (700-2500nm) has lower energy and higher penetration into biological tissues compared to visible light, giving it significant advantages and immense application value in fields such as biosensing (e.g., blood oxygen saturation, body fat percentage), AR / VR technology (e.g., eye tracking), remote sensing, and optical communication.

[0003] Near-infrared LED chips suffer from drawbacks such as low energy conversion efficiency, narrow emission half-width, and fixed emission position, which severely limit their application and development in LEDs, especially micro-LEDs. To address this issue, scientists have proposed the concept of light-conversion LEDs, employing a strategy of combining blue LED chips with near-infrared phosphors to fabricate highly efficient and flexible near-infrared LEDs. Since commercial blue LED chips are relatively mature, the quality of the near-infrared phosphor becomes the core factor affecting the final LED device. Through research over the past decade, scientists have developed various near-infrared phosphors, such as transition metal ion systems (Cr... 3+ ,Cr 4+ ,Fe 3+ Ni 2+ and Mn 4+ etc.), rare earth ion system (Eu 2+ ,Nd 3+ ,Yb 3+ ,Pr 3+ , and Tm 3+ etc.), ns 2 Configurational ion system (Sn) 2+ ,Bi 2+Near-infrared phosphors (including those made of organic materials and quantum dots) exhibit good stability and quantum yield, but most are in powder or bulk form, greatly limiting their application in micro-LEDs. Organic molecules possess good plasticity but suffer from low luminous efficiency and poor stability. In contrast, quantum dots possess advantages such as nanoscale size, tunable emission wavelength, wide excitation range, large absorption cross-section, and high quantum yield, making them a widely studied and promising light conversion material. Therefore, quantum dots are an ideal phosphor for near-infrared micro-LEDs.

[0004] Currently, the near-infrared quantum dots studied are mainly group II-VI and IV-VI semiconductors, such as CdSe, CdTe, and PbSe. Although they have good optical properties, the presence of heavy metal elements (Cd) in their composition is a concern. 2+ and Pb 2+ Pb / Cd-free near-infrared quantum dot phosphors are strictly restricted by countries and regions such as the United States and the European Union. Currently, Pb / Cd-free near-infrared quantum dot phosphors mainly suffer from low quantum yield (<70%) and poor photothermal stability, which greatly limits the light conversion efficiency and lifespan of devices. In 2020, Liu et al. first applied non-toxic quantum dots to near-infrared mini-LEDs (Chem. Commun. 2020, 56, 8285), but due to poor stability, the highest LED irradiation power was only 10.9 mW. There are currently no reports on the application of non-toxic quantum dots to near-infrared micro-LEDs. Furthermore, avoiding coffee rings, ensuring uniform dispersion and stability of the phosphor, and controlling and repeating the morphology and size of the micron-scale array are all core problems facing near-infrared quantum dot micro-LEDs. Therefore, developing a class of non-toxic, efficient, and stable quantum dot phosphors, and controlling the assembly of the phosphors at the micron scale, is crucial for the development of near-infrared micro-LEDs. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this invention provides a method for preparing near-infrared quantum dots for light-emitting devices and their application in LEDs, especially near-infrared quantum dots for mini-LEDs and micro-LEDs.

[0006] In a first aspect, the present invention provides a near-infrared quantum dot for a light-emitting device, wherein the quantum dot may be selected from CuInSe2, CuInTe2, AgInSe2, AgInTe2, CuInSe2:Zn 2+ CuInTe2:Zn 2+ AgInSe2:Zn 2+ AgInTe2:Zn 2 +, CuInSe2@ZnS, CuInTe2@ZnS, AgInSe2@ZnS, AgInTe2@ZnS, CuInSe2:Zn 2+ @ZnS、CuInTe2:Zn 2+ @ZnS、AgInSe2:Zn 2+ @ZnS、AgInTe2:Zn 2+ @ZnS, AgInSe2@ZnSe, AgInTe2@ZnSe, CuInSe2:Zn 2+ @ZnSe、CuInTe2:Zn 2+ @ZnSe、AgInSe2:Zn 2+ @ZnSe and AgInTe2:Zn 2+ One or more of the @ZnSe quantum dots, preferably AgInSe2@ZnSe, AgInTe2@ZnSe, or CuInSe2:Zn 2+ @ZnSe、CuInTe2:Zn 2+ @ZnSe and AgInSe2:Zn 2 + One or more of @ZnSe, for example, CuInSe2:Zn 2+ @ZnSe Quantum Dots

[0007] According to an embodiment of the present invention, the quantum dot can be excited by light of 250-600nm to emit near-infrared light with a wavelength of 650-1500nm, an emission peak in the range of 700-1300nm, and a half-width at half-maximum of more than 170nm. Preferably, the emission wavelength of the quantum dot is 650-1000nm and the emission peak is 700-800nm.

[0008] According to an embodiment of the present invention, the average particle size of the quantum dots is 1 to 30 nm, for example 6 nm.

[0009] According to an embodiment of the present invention, the fluorescence quantum yield of the quantum dot is greater than 80%, preferably greater than 85%, and more preferably greater than 92%, for example 92.8%.

[0010] According to an embodiment of the present invention, the quantum dots can maintain more than 80% of their luminescence intensity after being stored at room temperature for 150 days, preferably more than 85% of their luminescence intensity. For example, the CuInSe2:Zn 2+ @ZnSe quantum dots can still maintain 86.9% of their luminescence intensity after 150 days.

[0011] Secondly, the present invention provides a method for preparing near-infrared quantum dots as described above, including preparing the quantum dots by thermal injection, solvothermal method or ion exchange method, with thermal injection as an example.

[0012] AInB2:aZn was prepared by hot injection method 2+ @ZnSe includes the following steps:

[0013] S1. Mix salt A, salt In, and optionally, salt Zn with a solvent to obtain a first solution. Add a second solution containing powder B to the solution and react to obtain AInB2:aZn. 2+ Where A is selected from Ag or Cu, B is selected from Se or Te, and a is 0 or 1;

[0014] S2. Add the Zn salt containing the shell-forming Zn salt to AInB2:aZn 2+ The mixture was stirred to obtain a third solution. A fourth solution containing Se powder was then added to the third solution and mixed. The reaction yielded AInB2:aZn. 2+ @ZnSe.

[0015] According to an embodiment of the present invention, in step S1, the A salt, In salt and Zn salt are all soluble salts, and the B powder is Se powder or Te powder.

[0016] According to an embodiment of the present invention, in step S1, the molar ratio of Cu / In is greater than 0.0 and less than or equal to 1.2, and the molar ratio of Zn / In is greater than 0.0 and less than or equal to 1.0, for example, Cu / In = 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, and Zn / In = 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0.

[0017] According to an embodiment of the present invention, the solvent is selected from a mixture of oleic acid, oleylamine, dodecyl mercaptan and octadecene.

[0018] According to an embodiment of the present invention, the mixing in step S1 is carried out under anhydrous and oxygen-free conditions, and the mixing temperature is 100-140°C, preferably 110-130°C, for example 120°C.

[0019] According to an embodiment of the present invention, in step S1, when B is Se, the second solution is prepared as follows: Se powder is added to a mixture of oleylamine and dodecyl mercaptan and dissolved. Preferably, the volume ratio of oleylamine to dodecyl mercaptan is (2-3):1, and more preferably, the volume ratio of oleylamine to dodecyl mercaptan is (2.1-2.6):1, for example, 2:1, 2.2:1, 2.3:1, 7:3, 2.5:1, 2.7:1.

[0020] According to an embodiment of the present invention, adding Se powder to a mixture of oleylamine and dodecyl mercaptan and dissolving it includes the following steps: adding Se powder to a mixture of oleylamine and dodecyl mercaptan and dissolving it by ultrasonication at room temperature.

[0021] According to an embodiment of the present invention, in step S1, when B is Te, the second solution is dissolved using a conventional dissolution method in the art.

[0022] According to an embodiment of the present invention, the reaction in step S1 includes the following steps: heating the first solution to a reaction temperature of 180-230°C, injecting the second solution, and reacting at the reaction temperature for 2-30 minutes.

[0023] According to an embodiment of the present invention, the reaction temperature in step S1 is 200-220°C and the reaction time is 15-25 min, for example, the reaction temperature is 180°C, 190°C, 210°C, or 220°C and the reaction time is 10 min, 15 min, 20 min, or 25 min.

[0024] According to an embodiment of the present invention, the preparation of the third solution in step S2 includes the following steps: adding zinc stearate to the AInB2:aZn obtained in step S1. 2+ In the solution, a mixed solvent is added to remove water and oxygen from the reaction system.

[0025] According to an embodiment of the present invention, the mixed solvent includes oleic acid, oleylamine, and octadecene.

[0026] According to an embodiment of the present invention, the mixing of the mixed solvent is carried out at a temperature of 100 to 150°C, preferably at 110 to 120°C, for example at 120°C.

[0027] According to an embodiment of the present invention, the preparation method of the fourth solution in step S2 is the same as the preparation method of the second solution when B is Se.

[0028] According to an embodiment of the present invention, in step S2, a fourth solution is added to the third solution and mixed. The reaction includes the following steps: first, the third solution is heated to 170-210°C, and then the fourth solution is added and reacted for 70-90 minutes.

[0029] According to an embodiment of the present invention, after step S2, the following steps are further included: washing the reaction product and centrifuging to obtain quantum dots.

[0030] Thirdly, the present invention provides a phosphor for a light-emitting device, the phosphor comprising near-infrared quantum dots as described above.

[0031] Fourthly, the present invention provides an application of the above-mentioned near-infrared quantum dots or phosphors in photoluminescence, preferably for LEDs, such as for mini-LEDs or micro-LEDs.

[0032] Fifthly, the present invention provides a mini-LED, wherein the mini-LED is provided with near-infrared quantum dots or phosphors as described above.

[0033] According to an embodiment of the present invention, the mini-LED includes an LED chip, on which near-infrared quantum dots or phosphors are disposed.

[0034] According to an embodiment of the present invention, the preparation method of setting near-infrared quantum dots or phosphors on an LED chip is as follows: mixing quantum dots or phosphors with an adhesive solution and coating them on the LED chip to form a quantum dot or phosphor layer, wherein the layered structure is a continuous or discontinuous structure.

[0035] According to an embodiment of the present invention, the near-infrared quantum dots or phosphors can be uniformly dispersed in the adhesive solution. For example, after the quantum dots are mixed with the adhesive solution, they have essentially the following properties: Figure 7 The transmission electron microscope image shown is a transmission electron microscope image.

[0036] According to an embodiment of the present invention, the mass ratio of the near-infrared quantum dots or phosphors mixed with the encapsulating adhesive is 5 to 40 mg / g, for example 25 mg / g.

[0037] Preferably, the LED chip can be a violet, blue, or red light chip, with a blue light chip being an example.

[0038] According to an embodiment of the present invention, the adhesive can be a thermosetting adhesive or a UV-curing adhesive, for example, a UV-curing adhesive.

[0039] According to an embodiment of the present invention, an isolation layer is provided between the near-infrared quantum dot or phosphor layer and the LED chip.

[0040] According to an embodiment of the present invention, a protective layer is provided on the near-infrared quantum dot or phosphor layer.

[0041] According to an embodiment of the present invention, the mini-LED has a basic shape as shown in the figure. Figure 7 The diagram shows the irradiance flux under double 85 aging (referring to conditions of 85°C and 85% humidity).

[0042] In a sixth aspect, the present invention also provides a micro-LED, wherein the micro-LED light-emitting device includes an LED chip, and the LED chip is provided with near-infrared quantum dots or phosphors as described above.

[0043] According to an embodiment of the present invention, the method for fabricating the micro-LED includes the following steps:

[0044] a) Near-infrared quantum dots or phosphors are dispersed in printing solvents to form ink;

[0045] b) Use ink to print on LED chips to form micro-LEDs.

[0046] According to an embodiment of the present invention, the printing solvent is selected from one or more solvents selected from octane, decanane, dodecane, dodecyl mercaptan, ethylene glycol, o-dichlorobenzene, cyclohexylbenzene and polytetrafluoroethylene, for example, polytetrafluoroethylene.

[0047] According to an embodiment of the present invention, the mass ratio of quantum dots or phosphors to solvent in the ink is 10-60 mg / g, for example 20 mg / g.

[0048] According to an embodiment of the present invention, the quantum dots can be uniformly dispersed in a printing solvent, for example, the ink has a substantially similar structure. Figure 12 The transmission electron microscope image shown is a transmission electron microscope image.

[0049] According to an embodiment of the present invention, the quantum dots can be printed on the chip by inkjet printing, electrohydraulic inkjet printing or transfer technology, for example, electrohydraulic inkjet printing.

[0050] According to an embodiment of the present invention, the LED chip can be a violet light, blue light, or red light chip, with a blue light chip being an example.

[0051] According to an embodiment of the present invention, before step b), the following step is further included: spin-coating a contact layer on the surface of the light-transmitting layer of the LED chip, wherein the contact angle between the contact layer and the ink is 10 to 30°, preferably 10 to 20°, for example 19.75°.

[0052] According to an embodiment of the present invention, the hydrophobic layer material is selected from at least one of PEDOT (3,4-ethylenedioxythiophene monomer), PMMA (polymethyl methacrylate) or PPy (polypyrrole), for example, PEDOT.

[0053] As an example, step b) includes the following steps: printing quantum dot ink onto the contact layer, and finally spin-coating a layer of UV-curable adhesive onto the quantum dot layer for protective encapsulation.

[0054] According to an embodiment of the present invention, the outer diameter of the needle used for electrohydraulic printing can be 50 μm, 20 μm, 10 μm, 5 μm, 2 μm and 1 μm, with 2 μm as an example.

[0055] According to an embodiment of the present invention, the quantum dots are formed into a dot matrix structure or a linear structure on an LED chip.

[0056] According to an embodiment of the present invention, each dot in the dot matrix structure is a light-emitting pixel, the diameter of the light-emitting pixel is less than 30 μm, preferably less than 20 μm, and more preferably less than 5 μm.

[0057] According to an embodiment of the present invention, the line width of the linear structure is less than 30 μm, preferably less than 20 μm, and more preferably less than 5 μm.

[0058] According to an embodiment of the present invention, the micro-LED has a basic shape as shown in the figure. Figure 17 Or the fluorescence image described in 18.

[0059] The beneficial effects of this invention are as follows:

[0060] This invention has the following advantages: 1) The near-infrared quantum dot phosphor has good photothermal stability, with a yield of over 80%, reaching up to 92.8%. It has high light absorption efficiency, effectively prevents blue light leakage, can be excited by various chips (UV, blue, and red), has wide applicability, excellent resistance to damp heat, and a long service life; 2) The near-infrared quantum dots in this invention do not contain toxic Pb / Cd heavy metals, conforming to the concept of green chemistry; 3) The quantum dots maintain excellent dispersibility in encapsulation adhesives and inkjet inks, preventing luminescence quenching caused by aggregation; 4) Quantum dot luminescent arrays with a size less than 30 μm can be prepared, exhibiting high luminescence intensity, regular shape, and no coffee rings, compared to... The chip cutting and mass transfer process is simpler, cheaper, and more repeatable, enabling large-scale production; 5) The inventors unexpectedly discovered that when preparing the core structure of near-infrared quantum dots, only when the oleylamine and dodecyl mercaptan used to dissolve Se powder are in a specific ratio (2-3):1 can near-infrared quantum dots with a quantum yield greater than 90% be obtained. Under other ratio conditions, the quantum yield drops sharply; 6) In this invention, when quantum dots are used in micro-LEDs, they are first configured into ink and then printed onto the surface of the LED chip. The contact angle between the contact layer on the LED chip surface and the ink is 10-30°, which makes the ink print without trailing and forms a uniform structure. Attached Figure Description

[0061] Figure 1 The CuInSe2:Zn prepared in Example 1 of this invention 2+ Excitation and emission spectra of @ZnSe quantum dots.

[0062] Figure 2The CuInSe2:Zn prepared in Example 1 of this invention 2+ Transmission electron microscopy image of ZnSe quantum dots dispersed in n-hexane.

[0063] Figure 3 The CuInSe2:Zn prepared in Example 1 of this invention 2+ Quantum dots and CuInSe2:Zn 2+ The graph shows the change in luminescence intensity of ZnSe quantum dots over time.

[0064] Figure 4 The graph shows a comparison of emission spectra and quantum yields for Examples 1, 2, and 3.

[0065] Figure 5 The CuInSe2:Zn synthesized in Example 1 and Comparative Example 1 of this invention 2+ @ZnSe quantum dot emission spectrum.

[0066] Figure 6 The CuInSe2:Zn synthesized in Example 1 and Comparative Example 2 of this invention 2+ CuInSe2:Zn 2+ @ZnSe and CuInSe2:Zn 2+ @ZnS quantum dot emission and quantum yield comparison chart.

[0067] Figure 7 CuInSe2:Zn in Embodiment 4 of the present invention 2+ Transmission electron microscopy image of ZnSe quantum dots in UV-curable adhesive.

[0068] Figure 8 This is a schematic diagram of the structure of the near-infrared mini-LED prepared in Example 4 of the present invention.

[0069] Figure 9 The graph shows the change in irradiance flux over time of the near-infrared mini-LED prepared in Example 4 of this invention under dual 85 aging.

[0070] Figure 10 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 3 of the present invention in a mini-LED coating solution.

[0071] Figure 11 This is a comparison of the operating spectra and irradiation flux of the mini-LEDs prepared in Example 4 and Comparative Example 3 of the present invention.

[0072] Figure 12 This is a transmission electron microscope image of quantum dots in micro-LED inkjet ink from Example 5 of the present invention.

[0073] Figure 13This is a schematic diagram of the near-infrared micro-LED structure in Embodiment 5 of the present invention.

[0074] Figure 14 This is a high-magnification image of the dot matrix printed in Comparative Example 4 of this invention.

[0075] Figure 15 This is a dot matrix scanning electron microscope image of Comparative Example 5 of the present invention.

[0076] Figure 16 This is a scanning electron microscope image of the micro array printed in Embodiment 5 of the present invention.

[0077] Figure 17 This is a micro-array fluorescent image printed in Embodiment 5 of the present invention.

[0078] Figure 18 Bright-field and fluorescent images of micro pentagrams and wavy lines printed in Embodiment 5 of the present invention. Detailed Implementation

[0079] The quantum dots, their preparation methods, and applications according to the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0080] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0081] Example 1

[0082] CuInSe2:Zn 2+ The preparation method of @ZnSe quantum dot phosphor is as follows:

[0083] 1) Add 0.1 mmol of cuprous iodide, 0.2 mmol of indium acetate, and 0.2 mmol of zinc acetate to a three-necked flask (Cu / In = 0.5, Zn / In = 1.0), then add 0.8 mL of oleic acid, 0.8 mL of oleylamine, 1 mL of dodecyl mercaptan, and 10 mL of octadecene to dissolve (oleic acid, oleylamine, dodecyl mercaptan, and octadecene ratio: 0.8:0.8:1:10). Heat to 120°C under nitrogen purging with stirring, and circulate under vacuum / nitrogen purging five times to remove water and oxygen from the system, yielding a light yellow first solution. Dissolve 0.4 mmol of selenium powder in a mixture of 0.7 mL of oleylamine and 0.3 mL of dodecyl mercaptan (oleylamine to dodecyl mercaptan 7:3), and sonicate at room temperature for 20 min until fully dissolved, yielding a brownish-red second solution.

[0084] 2) Heat the first solution to 220°C, then rapidly inject the second solution into it. Maintain the reaction at 220°C for 20 minutes, then cool to room temperature in an ice-water bath to obtain an intermediate product solution. The intermediate product is CuInSe2:Zn. 2+ Quantum dots.

[0085] 3) Add 0.3 mmol of zinc stearate to the intermediate product solution obtained in 2), then add 0.4 mL of oleic acid, 0.2 mL of oleylamine, and 10 mL of octadecene. Heat to 120°C under nitrogen purging with stirring, and cycle under vacuum / nitrogen purging five times to remove water and oxygen from the system, yielding the third solution. Dissolve 0.4 mmol of selenium powder in a mixture of 0.5 mL of oleylamine and 0.5 mL of dodecanethiol, and sonicate at room temperature for 20 min until fully dissolved, yielding the fourth solution.

[0086] 4) After heating the third solution to 200℃, add the fourth solution dropwise over 1 hour, maintain the temperature at 200℃ for another 30 minutes, and then cool to room temperature in an ice-water bath to obtain the reaction product solution. The reaction product is CuInSe2:Zn. 2+ @ZnSe.

[0087] 5) Wash the reaction product from step 4) with a mixture of ethanol and n-hexane (ethanol to n-hexane volume ratio 1:1), and centrifuge to obtain CuInSe2:Zn. 2+ @ZnSe quantum dot phosphor, dispersed in n-hexane for storage.

[0088] Figure 1 The CuInSe2:Zn is given. 2+ The excitation and emission spectra of @ZnSe quantum dots show that the quantum dots exhibit a broadband excitable characteristic from 250-600 nm, and the emission spectrum is from 600 to 1000 nm.

[0089] Figure 2 The CuInSe2:Zn is given. 2+ The transmission electron microscopy image of ZnSe quantum dots dispersed in n-hexane shows that the quantum dots are tetrahedral in shape, uniform in size, with an average particle size of about 6 nm, and have good monodispersity.

[0090] Figure 3 The CuInSe2:Zn is given. 2+ The graph shows the change in luminescence intensity over time before and after coating the CuInSe2:Zn quantum dots. It can be seen that the intensity of luminescence before coating is significantly higher than that before coating. 2+ Quantum dots exhibited complete quenching of luminescence after 40 days of storage at room temperature, while CuInSe2:Zn... 2+ @ZnSe quantum dots can still maintain 86.9% of their luminescence intensity after 150 days, indicating that the ZnSe shell can significantly improve the stability of quantum dot phosphors.

[0091] Example 2

[0092] The difference between this embodiment and Example 1 is that the amount of materials added in step 1) is changed to: 0.08 mmol cuprous iodide, 0.2 mmol indium acetate and 0.16 mmol zinc acetate are added to a three-necked flask (Cu / In = 0.4, Zn / In = 0.8), and then 0.6 mL oleic acid, 0.6 mL oleylamine, 0.8 mL dodecyl mercaptan and 10 mL octadecene are added to dissolve (the ratio of oleic acid, oleylamine, dodecyl mercaptan and octadecene is 0.6:0.6:0.8:10); the reaction conditions in step 2) are changed to: the reaction is carried out at 200°C for 25 min, and all other steps are the same as in Example 1.

[0093] Example 3

[0094] The difference between this embodiment and Example 1 is that the amount of materials added in step 1) is changed as follows: 1.2 mmol of cuprous iodide, 0.2 mmol of indium acetate and 0.1 mmol of zinc acetate are added to a three-necked flask (Cu / In = 0.6, Zn / In = 0.5), followed by the addition of 1 mL of oleic acid, 1 mL of oleylamine, 1 mL of dodecyl mercaptan and 10 mL of octadecene (the ratio of oleic acid, oleylamine, dodecyl mercaptan and octadecene is 1:1:1:10). The reaction conditions in step 2) are changed to: the reaction is carried out at 230°C for 15 min, and all other steps are the same as in Example 1.

[0095] Figure 4 The graph shows a comparison of the emission spectra and quantum yields of quantum dots from Examples 1, 2, and 3. It can be seen that the CuInSe2:Zn synthesized with different feed ratios exhibits varying yields. 2+ The emission peak positions of the ZnS quantum dots show slight shifts: in Example 1, the peak is at 741 nm; in Example 2, it is at 718 nm; and in Example 3, it is at 770 nm, all located in the near-infrared region. Furthermore, the quantum yield can reach over 80% (92.8% in Example 1, 84.1% in Example 2, and 80.7% in Example 3). This indicates that the quantum dots prepared by this invention have a high quantum yield.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that the selenium powder in steps 1) and 3) is dissolved in 0.5 mL of oleylamine and 0.5 mL of dodecyl mercaptan (oleylamine and dodecyl mercaptan 1:1), while the other steps are the same as in Example 1.

[0098] like Figure 5 As shown in the comparative test, the luminescence intensity of the quantum dot phosphor prepared in Comparative Example 1 was only half that of Example 1, indicating that the ratio of oleylamine to dodecathiol in the dissolved selenium powder significantly affects the CuInSe2:Zn ratio. 2+The luminescence efficiency of ZnSe quantum dots is significantly affected.

[0099] Comparative Example 2

[0100] Preparation of CuInSe2:Zn 2+ @ZnS quantum dot phosphor: The difference between this comparative example and Example 1 is that the selenium powder in step 3) is replaced with sulfur powder.

[0101] Figure 6 The CuInSe2:Zn is given. 2+ Quantum dots and CuInSe2:Zn 2+ @ZnSe and CuInSe2:Zn 2+ @ZnS quantum dot emission and quantum yield comparison chart. Compared to CuInSe2:Zn 2+ Quantum dots, CuInSe2:Zn 2+ @ZnSe and CuInSe2:Zn 2+ The emission peak position of the ZnS quantum dot does not change significantly; CuInSe2:Zn 2+ The quantum yield is 28.6%, for CuInSe2:Zn containing ZnSe. 2 + The quantum yield of ZnSe increased to 92.8%, while that of CuInSe2:Zn containing ZnS increased. 2+ The quantum yield of ZnS only increased to 46.9%, indicating that the ZnSe shell has a better effect on improving luminescence efficiency.

[0102] Example 4

[0103] Based on CuInSe2:Zn 2+ The preparation method of near-infrared mini-LED using ZnSe quantum dot phosphor is as follows:

[0104] 1) Take 25 mg of CuInSe2:Zn prepared in Example 1 2+ @ZnSe quantum dots were dispersed in 5 mL of chloroform, and then 1 g of UV-curable adhesive was added. The mixture was sonicated for 10 min and then evaporated in chloroform using a rotary evaporator to obtain the mini-LED quantum dot coating solution.

[0105] 2) First, uniformly coat 15mg of UV-curable adhesive onto the 2835 LED chip and cure it under UV light for 10 minutes to form an isolation layer; then uniformly coat 60mg of quantum dot coating liquid onto the isolation layer and cure it under UV light for 10 minutes to form a quantum dot layer; finally, uniformly coat 15mg of UV-curable adhesive onto the quantum dot layer and cure it under UV light for 10 minutes to form a protective layer, and encapsulate it into a mini-LED device.

[0106] Figure 7 The CuInSe2:Zn is given. 2+ The transmission electron microscopy image of @ZnSe quantum dots in UV-curable adhesive shows that the nanoparticles are well dispersed.

[0107] Figure 8 A schematic diagram of the near-infrared mini-LED structure is given.

[0108] Figure 9 The irradiance flux diagram of the near-infrared mini-LED prepared in this embodiment under dual 85 aging is given. As can be seen from the figure, the irradiance flux of the mini-LED prepared in this embodiment can still reach 94.5% even when the aging time is greater than 70h.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 2 is that chloroform in step 1) is replaced with n-hexane, while the other steps are the same as in Example 2, and a mini-LED device is prepared.

[0111] Figure 10 The transmission electron microscope (TEM) image of the quantum dot-UV colloid mixture prepared in this comparative example shows that the quantum dots are in an aggregated state. The operating spectra and irradiance of the mini-LEDs prepared in Comparative Example 4 and Comparative Example 3 are compared. Figure 11 As shown, the irradiance of the mini-LED prepared in Comparative Example 3 was 10.3 mW @ 350 mA, and the irradiance of the mini-LED prepared in Example 4 was 88.7 mW @ 350 mA, indicating that the uniform dispersion of quantum dot phosphor is very important for the output efficiency of LED devices. The CuInSe2:Zn-based LED prepared in Example 4... 2+ The optimal irradiance of the ZnSe quantum dot phosphor near-infrared mini-LED (88.7 mW @ 350 mA) also exceeds the highest irradiance value reported in the literature for non-toxic quantum dot near-infrared mini-LEDs.

[0112] Example 5

[0113] Based on CuInSe2:Zn 2+ The preparation method of near-infrared micro-LEDs using ZnSe quantum dot phosphors is as follows:

[0114] 1) Take 20 mg of CuInSe2:Zn prepared in Example 1 2+ @ZnSe quantum dots were dispersed in 5 mL of cyclohexane, and then 1 g of a mixture of polytetrafluoroethylene (PTFE) and thinner (PTFE mass fraction 48%) was added. The mixture was ultrasonically mixed for 10 min, and the cyclohexane was evaporated using a rotary evaporator to obtain the quantum dot inkjet printing ink. The viscosity of the inkjet printing ink was 230 cP.

[0115] 2) Spin-coat a layer of PEDOT (3000 r / min, 1 min) onto the surface of the LED chip's light-transmitting layer, and dry at 150℃ for 15 min to obtain the inkjet printing substrate. The contact angle between the inkjet printing ink and the substrate is 19.74°.

[0116] 3) Then, the quantum dot ink is loaded into the printing needle with a needle orifice diameter of 2μm, a needle tip distance of 18μm from the substrate, a printing speed of 1mm / s, an ink opening delay of 30ms, an ink drop delay of 120ms, an ink closing delay of 50ms, a bias of 430V, a frequency of 100Hz, and a duty cycle of 20%. The quantum dot ink is then printed onto the PEDOT surface to form a micron-scale micro light conversion array with a regular shape and uniform dispersion.

[0117] 4) After drying the product from step 3) at 75°C for 30 minutes, spin-coat a layer of encapsulating adhesive on the outermost layer to encapsulate it into a micro-LED device.

[0118] Figure 12 The CuInSe2:Zn is given. 2+ A transmission electron microscope image of ZnSe quantum dots in inkjet printing ink shows CuInSe2:Zn 2+ @ZnSe quantum dots exhibit good dispersion and no aggregation.

[0119] Figure 13 A schematic diagram of the near-infrared micro-LED structure is given.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 5 is that the polytetrafluoroethylene and thinner mixture in step 1) is replaced with a mixture of n-octane and dodecane (n-octane and dodecane 3:7).

[0122] Figure 14 The high-magnification image of the dot matrix printed in Comparative Example 4 shows that the printed dots gradually become smaller, have obvious coffee rings, and also show clustering / needle-like shapes, indicating that the physicochemical properties of the printing ink are crucial to the shape and repeatability of the final micro array.

[0123] Comparative Example 5

[0124] The difference between this comparative example and Example 5 is that PEDOT in step 2) is replaced with PDMS.

[0125] Figure 15 The image shown is a scanning electron microscope (SEM) image of the dot matrix printed in Comparative Example 5. It can be seen that the printed dots exhibit severe tailing, and some dots are even completely interconnected, indicating that the affinity between the substrate and the printing ink is also crucial to the shape of the final microarray.

[0126] Figure 16 Scanning electron microscope (SEM) images of the microarray printing in Example 5 are provided. It can be seen that the printed dots have regular and complete shapes, uniform size, and good repeatability; the printed straight lines also exhibit good morphology and stability. Figure 17 As can be seen, the microarray printed in Example 3 exhibits a strong and uniform fluorescence signal. Additionally, Figure 18 The paper also demonstrates the printing effect of Example 5 on complex shapes. It can be seen that even when printing pentagrams or wavy lines, the structure remains uniform and complete, with good fluorescence signal. This indicates that the method's printing of entire arrays has excellent controllability and stability. Notably, the dot matrix diameter printed in Example 5 is less than 5 μm, exceeding that of current commercial inkjet printing technologies (10-30 μm). This also marks the first time that non-toxic quantum dots have been used in near-infrared micro-LED arrays below 5 micrometers.

[0127] The specific embodiments of the present invention have been described above by way of example. However, the scope of protection of the present invention is not limited to the above exemplary embodiments. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing near-infrared quantum dots for light-emitting devices, characterized in that, CuInSe2:Zn prepared by hot injection method 2+ @ZnSe includes the following steps: S1. A first solution is obtained by mixing Cu salt, In salt, and Zn salt with a solvent. A second solution containing Se powder is then added to react the mixture, yielding CuInSe2:Zn. 2+ ; The solvent is a mixed solvent of oleic acid, oleylamine, dodecyl mercaptan and octadecene; The second solution is prepared as follows: Se powder is added to a mixture of oleylamine and dodecyl mercaptan and dissolved, wherein the volume ratio of oleylamine to dodecyl mercaptan is (2~3):1; S2. Add Zn salt to CuInSe2:Zn 2+ The mixture is stirred to obtain a third solution. A fourth solution containing Se powder is then added to the third solution and mixed. The reaction yields CuInSe2:Zn. 2+ @ZnSe; The fluorescence quantum yield of the quantum dots is greater than 80%.

2. The preparation method according to claim 1, characterized in that, The quantum dots can be excited by light of 250-600 nm and emit near-infrared light with wavelengths of 650-1500 nm and emission peaks in the range of 700-1300 nm.

3. The preparation method according to claim 1, characterized in that, The quantum dots can maintain more than 80% of their luminescence intensity after being stored at room temperature for 150 days.

4. The preparation method according to any one of claims 1-3, characterized in that, In step S1, the molar ratio of Cu / In is greater than 0.0 and less than or equal to 1.2, and the molar ratio of Zn / In is greater than 0.0 and less than or equal to 1.

0. And / or, the reaction in step S1 includes the following steps: heating the first solution to a reaction temperature of 180~230℃, injecting the second solution, and reacting at the reaction temperature for 2~30 min.

5. The preparation method according to any one of claims 1-3, characterized in that, The preparation of the third solution in step S2 includes the following steps: adding zinc stearate to the CuInSe2:Zn obtained in step S1. 2+ The solution is mixed with a mixed solvent to remove water and oxygen from the reaction system. The mixing process is carried out at a temperature of 100~150℃.

6. The preparation method according to any one of claims 1-3, characterized in that, In step S2, a fourth solution is added to the third solution and mixed. The reaction includes the following steps: first, the third solution is heated to 170~210℃, and then the fourth solution is added and reacted for 70~90 minutes.

Citation Information

Patent Citations

  • Synthesis method of Zn-CuInSe2 / ZnSe core-shell quantum dots

    CN111518540A